(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Mobile Ad Hoc Networks (MANETs) have emerged as a flexible and infrastructure-independent communication technology capable of supporting military operations, disaster recovery, emergency response, intelligent transportation, healthcare monitoring, and mobile computing applications. Despite their advantages, the absence of centralized administration, dynamic topology changes, limited bandwidth, and node mobility expose MANETs to numerous routing attacks such as black hole, gray hole, wormhole, Sybil, and packet dropping attacks. Traditional secure routing protocols primarily rely on cryptographic mechanisms that effectively defend against external attacks but often fail to identify malicious or selfish nodes operating within the network. Trust management has therefore become an effective approach for enhancing routing security by evaluating node behavior during packet forwarding and route discovery. This experimental study proposes a Trust-Aware Secure Routing Protocol (TASRP) for Mobile Ad Hoc Networks that integrates trust evaluation, secure route discovery, authentication, node behavior monitoring, malicious node isolation, and routing performance evaluation into a unified computational framework. The proposed framework combines direct trust, indirect trust, route reliability, and communication efficiency to establish secure and trustworthy communication paths while minimizing routing overhead and packet loss. A mathematical framework and algorithmic strategy are developed to evaluate trust computation, packet delivery ratio, routing overhead, end-to-end delay, throughput, network lifetime, and overall routing security. Experimental evaluation demonstrates that the proposed trust-aware routing framework significantly improves communication reliability, attack resistance, packet delivery performance, and Quality of Service while reducing malicious packet forwarding and routing instability. The proposed protocol provides valuable guidance for researchers, communication engineers, and cybersecurity professionals seeking to design secure, scalable, reliable, and trust-aware routing solutions for Mobile Ad Hoc Networks.